Quercetin-3-oleoyl derivatives as new GPR40 agonists: Molecular docking studies and functional evaluation. Issue 14 (15th July 2019) - Carullo, Gabriele; Perri, Mariarita; Manetti, Fabrizio; Aiello, Francesca; Caroleo, Maria Cristina; Cione, Erika
Graphical abstract: Abstract: The G-protein-coupled receptor 40 (GPR40) is an attractive molecular target for the treatment of type 2 diabetes mellitus. Previously, based on the natural oleic acid substrate, an exogenous ligand for this receptor, named AV1, was synthesized. In this context, here we validated the activity of AV1 as a full agonist, while the corresponding catechol analogue, named AV2, was investigated for the first time. The ligand-protein interaction between this new molecule and the receptor was highlighted in the lower portion of the GPR40 groove that generally accommodates DC260126 . The functional assays performed have demonstrated that AV2 is a suitable GPR40 partial agonist, showing a therapeutic potential and representing a useful tool in the management of type 2 diabetes.